Islamophobia in Europe and its Global Impact - Adetry, Asrida; Burhanuddin, Agussalim (Glocal Society Journal, 2024)
Europe is the region with the highest incidence of anti-Muslim discrimination worldwide, primarily driven by policy issues, according to the 14th report on Islamophobia by the OIC, which documents Islamophobic attacks and anti-Muslim hatred between December 2020 and January 2022. The influence of European Islamophobia extends globally, contributing to what is known as the globalization of Islamophobia. This trend is significant as it illustrates the spread of anti-Muslim sentiment across the political spectrum on a global scale. This study aims to explore the development and manifestation of Islamophobia in Europe and analyze its impact on the rise of global Islamophobia. Utilizing a qualitative approach, the research was conducted from August 2023 to August 2024, with data gathered through a literature review. The paper argues that Islamophobia in Europe is expanding and manifests through six key indicators: discrimination, hate speech and online hatred, Islamophobic policies, right-wing political movements, verbal and physical attacks, and insults directed at the niqab, hijab, and burqa. Key factors influencing the global spread of Islamophobia include the Great Replacement conspiracy theory, white supremacist manifestos, right-wing parties promoting Islamophobic discourse, and the adoption of Islamophobic policies by other countries.